The effects of reading topic and topic preference on reading comprehension - Hesty Widiastuty (Universitas Islam Negeri Palangka Raya, Indonesia, 2011)
This study is aimed at investigating the interaction effect of reading topic and topic preference, the effect of reading topic, and the effect of topic preference on Physics score, Biology score, and Chemistry score of single cause-multiple effects text. The population of this study was the eleventh grade of IPA students of SMA Negeri 2 Kuala Kapuas in Academic Year 2008/2009. There were 64 students of two classes (XI IA1 and IX IA2) as the sample of this study chosen by using cluster random sampling. It was used experimental research with factorial experimental design. The data were processed and analyzed through these steps: taking the data, coding scoring, tabulating, analyzing the data by using statistic technique of ANOVA processed by using SPSS 15 and taking the conclusion based on the statistical result. The results show that: (1) there was significant interaction effect among reading topic and topic preference on Physics score, Biology score, and Chemistry score of single cause-multiple effects text, (2) there was no significance effect of reading topic of single cause-multiple effects text, and (3) there was no significance effect of topic preference on Physics score, Biology score, and Chemistry score of single cause-multiple effects text.